2013
DOI: 10.1155/2013/986073
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Girdin Protein Expression in Glioma

Abstract: Objective. To investigate the expression status of Girdin in glioma and the relationship between Girdin expression and the biological behavior of glioma. Materials and methods. The expression status of Girdin in glioma from 560 cases was evaluated by RT-PCR, Western Blot and immunohistochemistry. The relationship between Girdin expression and clinic-pathological parameters as well as prognosis was also studied. Results. The expression of Girdin in high grade glioma was significantly higher than low grade gliom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…9 ) in which integrin signaling is rewired in invasive cancer cells via activation of trimeric G proteins by the nonreceptor protein GIV. Previous work by us ( Ghosh et al, 2008 , 2010 ; Garcia-Marcos et al, 2011b ) and others ( Ling et al, 2011 ; Dunkel et al, 2012 ; Liu et al, 2012a ; Shibata et al, 2013 ; Zhao et al, 2013 ; Song et al, 2014 ; Wang et al, 2014 ) has established that GIV expression is up-regulated in invasive tumor cell lines and metastatic tumors, and that GIV is required for metastasis in mouse models ( Jiang et al, 2008 ). Here, we show that without GIV, invasive cancer cells display impaired actin remodeling, motility, and invasiveness in response to integrin stimulation, whereas expression of GIV in noninvasive cancer cells enhances integrin signaling and haptotaxis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…9 ) in which integrin signaling is rewired in invasive cancer cells via activation of trimeric G proteins by the nonreceptor protein GIV. Previous work by us ( Ghosh et al, 2008 , 2010 ; Garcia-Marcos et al, 2011b ) and others ( Ling et al, 2011 ; Dunkel et al, 2012 ; Liu et al, 2012a ; Shibata et al, 2013 ; Zhao et al, 2013 ; Song et al, 2014 ; Wang et al, 2014 ) has established that GIV expression is up-regulated in invasive tumor cell lines and metastatic tumors, and that GIV is required for metastasis in mouse models ( Jiang et al, 2008 ). Here, we show that without GIV, invasive cancer cells display impaired actin remodeling, motility, and invasiveness in response to integrin stimulation, whereas expression of GIV in noninvasive cancer cells enhances integrin signaling and haptotaxis.…”
Section: Discussionmentioning
confidence: 93%
“…; Ghosh et al, 2010 ; Garcia-Marcos et al, 2011b ; Dunkel et al, 2012 ) and is required for metastasis in mice ( Jiang et al, 2008 ). GIV expression in primary tumors also correlates with metastasis and predicts patient death in multiple cancers of epithelial origin ( Garcia-Marcos et al, 2011b ; Ling et al, 2011 ; Dunkel et al, 2012 ; Liu et al, 2012a ; Shibata et al, 2013 ; Zhao et al, 2013 ; Song et al, 2014 ; Wang et al, 2014 ), making it a bona fide metastasis-related protein. Thus, G protein activation by GIV’s GEF motif has emerged as a molecular function that underlies the pathological significance of GIV in cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Proliferation, migration and invasion of tumor cells are the main biological characteristics of malignant cancers, defining tumor growth and spread and, ultimately, disease prognosis (32). Girdin is highly expressed in a variety of malignant tumors, including glioma and breast, colon and lung cancers (25)(26)(27)(28), where it can promote proliferation, migration and invasion of tumor cells (22). In the present study, we found that the downregulation of Girdin expression in LoVo cells could inhibit cell proliferation, migration and invasiveness, indicating the critical role of Girdin in CRC, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Girdin is a novel multi-functional protein acting at the cross-roads of G protein-and tyrosine kinase receptor-mediated signaling (21), which has been shown to be involved in diverse biological processes, including cancer cell proliferation and spread, in particular through the activation of STAT3 (22)(23)(24). An increasing number of studies have demonstrated that Girdin is highly expressed in several types of cancers, including breast cancer (25), glioma (26), lung (27) and gastric cancer (28). In CRC, Girdin was shown to promote chemoresistance (29); however, the association between Girdin and CRC development remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Girdin is expressed at relatively high levels in brain gliomas. A previous study reported an association between the expression of girdin and glioma metastasis ( 14 ), and the expression levels of girdin correlate with the degree of malignancy in brain gliomas. However, the role of girdin in brain gliomas remains to be elucidated.…”
Section: Introductionmentioning
confidence: 96%